Imunoterapia clínica de células CAR-T usadas contra tumores – uma revisão sistemática - Pereira, Vinicius Alex Cano (Universidade Federal de São Carlos, 2023)
Chimeric antigen receptor T cell therapy (CAR-T cell therapy) is a type of immunotherapy for cancer treatment that involves genetically modifying the patient's own T cells to express a specific CAR for a tumor antigen, followed by ex vivo cell expansion and reinfusion into the patient. Although CAR-T cells represent a major advance in cancer treatment and have achieved unprecedented success in hematological malignancies, especially in relapsed/refractory B-cell malignancies (R/R), their success in solid tumors is quite limited due to factors such as the highly immunosuppressive tumor microenvironment, low CAR-T cell infiltration, and toxicities. In this systematic review we evaluate the recents CAR-T cells clinical trials tested for different malignancies to overview recent advances in cancer immunotherapy using this approach. We sourced CAPES database, web of science and Pubmed through the following keywords: “Immunotherapy” AND “CAR T cells” and “Solid tumors” AND “CAR T cells”. Some criterions was established to compose this review as the articles had to be published between 2015 and 2021, it must be clinical trials researchers available and published in English language. Review and pre-clinical research articles are both excluded. PRISMA systematic review for clinical trials was consulted and followed to help the discussion and data presentation, and research website, as clinicaltrials.gov and fda.gov, as well as recent pre-clinical improvement CAR T cells were incorporated into the discussion. We obtained 1.188 articles, which 14 met inclusion/exclusion criteria and discussed CAR design, T cell production, and toxicities. Sample size is small but consistent with others reviews. Determinant factors for CAR-T activation and resistance to treatment were identified, including T cell concentration, disease/antigen burden, prior therapies, and CRS/ICANS adverse. Our study has shown that CAR-T cells have a great potential in threatening malignance, even some toxicities may occur. The CAR-T improvement must be continuous to ameliorate the Cell-Associated Neurotoxicity Syndrome/Immune effector Cytokine-Release Syndrome (CRS/ICANS) or even patient’s death, as well as overcome the solid malignance resistance. Several CAR-T cells strategies have been incorporated and developed to reach this goal and successfully has been tested into clinical practice. This evidentiates the high potential of this immunotherapy approach against cancer.
Clinical immunotherapy with CAR T cells used against tumors - a systematic review
Keywords: Tumors; Immunotherapy; CAR-T; Tumores; Imunoterapia; CIENCIAS BIOLOGICAS::IMUNOLOGIA::IMUNOLOGIA APLICADA; CIENCIAS BIOLOGICAS::IMUNOLOGIA::IMUNOLOGIA CELULAR